Hosting Early Study Abroad Students in Ontario: Internationalization of Education Dynamics in Secondary Schooling - Bell, Nancy; Tarc, Paul; Schecter, Sandra R.; Racco, Alyssa; Tang, Haoming (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2023)
This study illuminates the current policy and practice dynamics and tensions of school internationalization in the province of Ontario generated by the increasing presence of international students at the secondary school level, identified as early study abroad (ESA) students. It conducts a comparative thematic analysis of a set of interviews with school- and board-level stakeholders of internationalization alongside a critical policy analysis of a key provincial policy text. We find that ESA-based internationalization is largely run out of internationalization offices resourced to focus on student recruitment and administrative support, with oversight of homestay and custodianship being significant components. The more idealistic visions of school internationalization emphasized in provincial policy and some school discourse occur in a more reactive fashion. On-the-ground educational support of these newcomer ESA students is shouldered by schools and educators within their existing and limited capacities, while the intercultural dimensions and benefits remain largely aspirational.